(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article outlines new approaches to the teaching of the science of philosophy, which is the main task of raising the thinking abilities of people. An attempt was made to reveal how significant it is for the educational cluster and its achievements to be focused on the processes of this science.